THE EFFECT OF BOARD OF DIRECTOR, AUDIT COMMITTEE, AND MANAGERIAL OWNERSHIP ON THE FIRM VALUE - Huda, Muhammad Sholikhul (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2024)
The purpose of this study is to understand the impact of board of director, audit committees, and managerial ownership on company value for companies listed in BEI between 2017 and 2020. This research is a quantitative study using purposive sampling as a method of data collection. The IDX website and the websites of each company are the sources of the data, which is derived from their financial and sustainability reports. This study's sample consists of non-financial companies registered in BEI that publish sustainability reports on their own in stand-alone format for the years 2017–2020. The analysis technique uses multiple regression analysis. The results of the analysis show that the audit committee and director have a positive impact on the company's value. On the other hand, managerial ownership has not impact on firm value. The variable used in this research is unstable, thus it is hoped that the subsequent research will be able to increase the variable to measure the results.